Prevalence of S.epidermidis and S.aureus and their biofilm ability among Iraqi patients suffering from urinary tract infection - Fadhel, Ayah; Abureesha, Rasmia; Al-azzawi, Raghad (Iraqi Journal of Science, 2023)
Urinary tract infections (UTI) caused by methicillin resistant staphylococci are agrowing problem for many health care institutions especially when it correlates withbiofilms formation of these isolates on living and nonliving surfaces. The prevalenceof staphylococci from UTI were studied and it was found that S.epidermidis arehigher prevalence than S.aureus 55.5% ( 10 out of 18) and 26.6% ( 8 out of 30) weremethicillin resistant staphylococcus aureus isolates (MRSA) and methicillin resistantstaphylococcus epidermidis (MRSE), respectively. Biofilm formation on microtiterplates revealed that MRSE isolates was more efficient in biofilm production than itscounterpart MRSA.